The Principle of Horizontal Subsidiarity: Framing Notes for its Role in the Peruvian Economic System - Sánchez Povis, Lucio Andrés (2024)
This paper explores the principle of horizontal subsidiarity in the Peruvian legal system, highlighting its importance as a fundamental pillar to balance state intervention and individual freedom in the economy. Starting with the explicit enshrinement of this principle in Article 60 of the 1993 Constitution, the study analyses its application and the challenges it faces in practice, particularly in the economic and social spheres. The paper reviews the historical and doctrinal evolution of the concept of subsidiarity, from its roots in classical political philosophy to its development in the Social Doctrine of the Catholic Church, and how these influences are reflected in Peruvian regulations. The paper also examines the interpretations and applications of the principle of subsidiarity in the jurisprudence of the Constitutional Court and INDECOPI’s decision-making practice, including the implementation of the “subsidiarity test” as a tool to evaluate the legitimacy of state business activities. It is argued that while this principle has been crucial in limiting state intervention, its interpretation should be broader, encompassing not only economic aspects but also its impact on the promotion of fundamental rights and social cohesion. The paper concludes with a critical evaluation of current policies and proposes recommendations to strengthen the application of the principle of subsidiarity in Peru, promoting a framework of state intervention that respects individual autonomy and fosters balanced and sustainable development in all areas of society.